Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Penurunan Intensitas Nyeri Pada Ibu Post Sectio Caesaria 24 Jam Pertama - Nurfadlilah, Irma; Prijatni, Ida; Jamhariyah, Jamhariyah (Jember Maternal and Child Health Journal; Vol 1 No 1 (2024): Jember Maternal and Child Health Journal, 2024)
Pain is an unpleasant sensory and emotional experience and arises due to tissue damage due to incisions in post sectio caesarea mothers. one of the efforts to reduce pain in post sectio caesarea mothers is by providing breathing relaxation techniques. This study aims to determine the effect of deep breathing relaxation techniques on reducing pain intensity in post secito caesarea mothers. Methodology : the article used is a literature review with a systematic mapping study type. Article taken from data based google scholar. The population obtained from the data based was 168 articles then screened using PICOS and obtained as many as 5 articles consisting of five national articles, the research design used quasi-experimental and pre-experimental. Results : 5 articles showed that the average frequency of pain in post SC mothers decreased after being given deep breathing relaxation techniques with the results of 5 articles using univariate analysis in the form of numerical data, namely the mean before giving deep breathing relaxation techniques was 5.4 and after giving deep breathing relaxation techniques in to 2.40. The results of the analysis of the 5 articles show the effect of deep breathing relaxation techniques on reducing pain intensity in post-cesarean mothers in the first 24 hours with a p-value <?. Conclusion : giving deep breathing relaxation techniques can be used as a complementary therapy to reduce pain in post sectio caesarea mothers in the first 24 hours.